Defining and conceptualising the commercial determinants of health. Issue 10383 (8th April 2023) - Gilmore, Anna B; Fabbri, Alice; Baum, Fran; Bertscher, Adam; Bondy, Krista; Chang, Ha-Joon; Demaio, Sandro; Erzse, Agnes; Freudenberg, Nicholas; Friel, Sharon; Hofman, Karen J; Johns, Paula; et al.
Summary: Although commercial entities can contribute positively to health and society there is growing evidence that the products and practices of some commercial actors—notably the largest transnational corporations—are responsible for escalating rates of avoidable ill health, planetary damage, and social and health inequity; these problems are increasingly referred to as the commercial determinants of health. The climate emergency, the non-communicable disease epidemic, and that just four industry sectors (ie, tobacco, ultra-processed food, fossil fuel, and alcohol) already account for at least a third of global deaths illustrate the scale and huge economic cost of the problem. This paper, the first in a Series on the commercial determinants of health, explains how the shift towards market fundamentalism and increasingly powerful transnational corporations has created a pathological system in which commercial actors are increasingly enabled to cause harm and externalise the costs of doing so. Consequently, as harms to human and planetary health increase, commercial sector wealth and power increase, whereas the countervailing forces having to meet these costs (notably individuals, governments, and civil society organisations) become correspondingly impoverished and disempowered or captured by commercial interests. This power imbalance leads to policy inertia; although many policy solutions are available, they are not being implemented. Health harms are escalating, leaving health-care systems increasingly unable to cope. Governments can and must act to improve, rather than continue to threaten, the wellbeing of future generations, development, and economic growth.